Corduroy goes to school : a lift-the flap book - Freeman, Don (New York : Scholastic Inc., 2002)
Corduroy has a lot to do at school today. He has to feed the classroom petsm listen to a story, paint, have a snack, and help clean up.
Keywords: School -- Fiction; Children stories